2018
DOI: 10.1002/jmv.25270
|View full text |Cite
|
Sign up to set email alerts
|

High spontaneous clearance of symptomatic iatrogenic acute hepatitis C genotype 4 infection

Abstract: Acute hepatitis C (AHC) infection resolves spontaneously in 15% to 40% of patients. Factors favoring spontaneous viral clearance remain undefined. In this study, predictors of spontaneous viral clearance in patients with symptomatic AHC were investigated. Epidemiological, clinical, and virologic parameters were also examined. Patients with symptomatic AHC were enrolled and followed up prospectively. The patients were followed up every 2 weeks in the first month and then monthly for the following 5 months, with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Lack of association with these factors could be related to the lack of exact date of high-risk exposure to infection. 26 A third study found no association of SVC with age, sex, race & peak ALT level. 27 The limitation of the present study was the small sample size.…”
Section: Discussionmentioning
confidence: 95%
“…Lack of association with these factors could be related to the lack of exact date of high-risk exposure to infection. 26 A third study found no association of SVC with age, sex, race & peak ALT level. 27 The limitation of the present study was the small sample size.…”
Section: Discussionmentioning
confidence: 95%
“…This virus has the highest prevalence in Africa and Asia, where it is four times more prevalent than HIV, and hence, HCV has the potential to cause the next pandemic, as the mortality has reached over 500,000 per annum [5]. The incubation period of HCV ranges from weeks to several months, with an average of around 7 weeks until symptoms occur [6]. HCV infection is often asymptomatic, making it very difficult to detect in its early stage.…”
Section: Introductionmentioning
confidence: 99%
“…However, new HCV infections are usually asymptomatic [2]. Without treatment, around 30% (15-45%) of infected persons spontaneously clear the virus within 6 months of infection; however, different HCV genotypes may exhibit different spontaneous clearance rates [3]. The remaining 70% (55-85%) of persons will develop chronic HCV infection.…”
Section: Introductionmentioning
confidence: 99%